Regulation of drug metabolism and toxicity by multiple factors of genetics, epigenetics, lncRNAs, gut microbiota, and diseases: a meeting report of the 21st International Symposium on Microsomes and Drug Oxidations (MDO) - Ai-Ming Yu; Magnus Ingelman-Sundberg; Nathan J. Cherrington; Lauren M. Aleksunes; Ulrich M. Zanger; Wen Xie; Hyunyoung Jeong; Edward M. Morgan; Peter J. Turnbaugh; Curtis D. Klaassen; Aadra P. Bhatt; Matthew R. Redinbo; et al. (Elsevier, 2017)
Variations in drug metabolism may alter drug efficacy and cause toxicity; better understanding of the mechanisms and risks shall help to practice precision medicine. At the 21st International Symposium on Microsomes and Drug Oxidations held in Davis, California, USA, in October 2-6, 2016, a number of speakers reported some new findings and ongoing studies on the regulation mechanisms behind variable drug metabolism and toxicity, and discussed potential implications to personalized medications. A considerably insightful overview was provided on genetic and epigenetic regulation of gene expression involved in drug absorption, distribution, metabolism, and excretion (ADME) and drug response. Altered drug metabolism and disposition as well as molecular mechanisms among diseased and special populations were presented. In addition, the roles of gut microbiota in drug metabolism and toxicology as well as long non-coding RNAs in liver functions and diseases were discussed. These findings may offer new insights into improved understanding of ADME regulatory mechanisms and advance drug metabolism research.